2016
DOI: 10.1080/03007995.2016.1257983
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of health utility weights among elderly patients receiving breast-conserving surgery plus hormonal therapy with or without radiotherapy

Abstract: Background-The selection of the most appropriate treatment combinations requires the balancing of benefits and harms of these treatment options as well as the patients' preferences for the resulting outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…Moreover, patients who received postoperative radiotherapy, on average, tended to have a higher OS. This is consistent with the research conducted by Ali et al 13. As the average life expectancy in the United States continues to increase, the standard for “elderly” care may continue to rise.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, patients who received postoperative radiotherapy, on average, tended to have a higher OS. This is consistent with the research conducted by Ali et al 13. As the average life expectancy in the United States continues to increase, the standard for “elderly” care may continue to rise.…”
Section: Discussionsupporting
confidence: 91%
“…Several authors have already attempted to develop such a reference model for MBC treatments. These models were however limited to a specific setting or patient population [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because model design influences cost-effectiveness results, researchers and the European network for health technology assessment (Eunethta) have argued for increased consistency between cost-effectiveness assessments [ 14 17 ]. Eunethta consequently encourages adherence to the HTA Core model ® [ 18 ] and researchers have argued for the development of disease-specific reference models; a unique model which would be used for all economic evaluations in a specific disease area [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the absence of clear literature data, the generalization of evidenced-based medical practice may be tenuous, making decisions more susceptible to physician biases and marketbased influences [1][2][3] . Over the last years, we have witnessed a growing interest in the treatment of elderly cancer patients, and various studies have shown that they can well tolerate multimodality treatments, including high dose radiotherapy with curative intent [1][2][3][4][5] . An increasing number of studies showed that also stereotactic body radiotherapy, i.e.…”
mentioning
confidence: 99%
“…On the other hand, there is a potential benefit from adjuvant radiotherapy in patients with predicted 10-year cancer specific survival rates lower than 80% 18 . The concept of health utility weight was recently introduced by Ali et al 1 , who estimated and compared the health utility of breast-conserving surgery followed by hormone therapy and associated or not with post-operative radiotherapy. The authors used an algorithm to determine the health utility weight by using health-related quality-of-life questionnaires.…”
mentioning
confidence: 99%